Social Conflict Generating Ecological Developments in the Life of Lake Balaton in Recent Decades – Invertebrate invasions - Balogh, Csilla; G.-Tóth, László (Acta Scientiarum Socialium, 2013)
Social Conflict Generating Ecological Developments in the Life of Lake Balaton in Recent Decades – Invertebrate invasions Lake Balaton, the largest shallow lake in Central Europe, is a natural treasure of Hungary. Since the open of the Sió Channel, the lake has become more vulnerable against biological invasions. Invasive aquatic alien species especially bivalves can evoke serious threats through causing dramatic changes and promoting numerous direct and indirect system-wide effects. They create or modify habitats, alter species diversity, nutrient cycling and other ecosystem processes; by these they generate several social conflict. Here we discuss our recent knowledge obtained on some exotic invasive invertebrates in Lake Balaton: the zebra mussel (Dreissena polymorpha) and the amphipod Caspian mud shrimp (Chelicorophium curvispinum), which were the first two invaders, Dikerogammarus species, and the latest (the ninth) exotic invader from the Ponto-Caspian region, the quagga mussel (Dreissena bugensis). Finally, the exotic Asiatic Chinese pond mussel (Sinanodonta woodiana) is also noticed, as the decay of its population was the most serious problem related to tourist attraction in the last years. We underline the emerging importance of studying the invasive species in order to save the original and natural ecological status of Lake Balaton.
Keywords: biological invasions; dramatic changes; social conflict